The Impact of Macroeconomic Variables on Sectoral Indices in Indonesia - Bambang Sutrisno (ETIKONOMI, 2017)
This study aims to examine the effect of macroeconomic variables on sectoral indices in the Indonesian Stock Exchange. The difference in sensitiveness among sectors is an interesting issue to investigate this relationship in an emerging market, such as Indonesia. This study employs ordinary least square (OLS) as an estimation method with monthly time-series data from January 2005 to December 2014. The results document that the interest rate, inflation rate, and exchange rate simultaneously have a significant effect on sectoral indices in Indonesia. The interest rate partially shows a significant negative influence on all sectors except basic industry and chemical, finance, infrastructure, utilities, and transportation, and miscellaneous industry sectors. The inflation rate partially has no significant effect on all sectors. The exchange rate partially has a significant negative impact on all industries.DOI: 10.15408/etk.v16i1.4323